Mágicas matemáticas como metodologia de ensino - Alves, Amanda Gouveia (2015)
Studies show that students of elementary and high school have great difficulty in learn-ing math concepts. This work brings together didactical alternatives, such as mathemati-cal magic, so the math teacher can use them in order to promote greater interest and enchantment of their students with mathematics and some of its important contents.